The Development of Productivity Performance Models: Based on Self-efficacy, Trust, Systems Quality, and Information Quality. Study on Information Systems of PT Pindo Deli Paper Products - Indah Kartika Sandhi (International Conference On Law, Business and Governance (ICon-LBG), 2013)
This research proposes a development model that explains productivity performance impacts of IS at the individual level. This research aims to test productivity performaceâs model by adding new constructs such as self-efficacy, trust, system quality and information quality as well as analyze the causality impact among variabels of productivity performanceâs model in PT Pindo Deli Paper Products. The sample used were 265 respondent. The results show that all variabels in this research have significant impact to productivity performance. This development model can gain a fuller understanding of IS-productivity performance impact not only by using the IS and nature of IS use but also by including self-efficacy, trust, system quality and information quality. The theoritical contribution of this research lies in the development of a model for productivity performance impact of IS that have significantly higher explanatory power than the existing models.